Practical Experience with Planar Three-Electrode Sensors: Graphite Modified with Carbon Nanotubes vs. Boron-Doped Diamond - Metelka, Radovan; Svitáková, Martina; Grapci, Vjosa; Arbneshi, Tahir (BEST Servis, 2023)
This contribution summarizes the practical experience gained during the experiments with planar sensors manufactured by screen-printing and other technologies for the preparation of working electrodes. The electrochemical properties of sensors with working electrodes made of screen-printed graphite modified with multiwalled carbon nanotubes and boron-doped diamond, prepared by chemical vapor deposition, were examined and compared in the electroanalysis of nicotine, uric acid, guanine, and adenine. The differences in intensities of the analytical signals, their repeatability, and the shift of peak potentials are discussed with respect to the material and composition of the working and reference part of the sensors.
Praktická zkušenost s planárními tříelektrodovými senzory: grafit modifikovaný uhlíkovými nanotrubičkami vs. borem dopovaný diamant
Keywords: Screen-printed carbon electrode; Boron-doped diamond electrode; Nicotine; Uric acid; Guanine; Adenine; Electroanalysis; Uhlíková tištěná elektroda; Borem dopovaná diamantová elektroda; Nikotin; Kyselina močová; Guanin; Adenin; Elektroanalýza